2017
DOI: 10.1111/faam.12116
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ Information Needs, Cost System Design, and Cost System Effectiveness in Dutch Local Government

Abstract: This study examines the relationships between stakeholders’ information needs, cost system design, and cost system effectiveness in local government, using a dataset of survey responses from 71 Dutch municipalities. Three cost system design characteristics are examined: (a) the complexity and (b) the inclusiveness of cost systems, and (c) their understandability for non‐financial internal users. These characteristics are shown to be only partly related to each other, and to differ in the extent to which they a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
2
25
0
4
Order By: Relevance
“…While both the Germanic and Napoleonic traditions have been resistant to managerialist ideas, these have penetrated the former more extensively than the latter (Painter and Peters 2010; Peters 2008). Furthermore, the Germanic administrative tradition (Germany, Austria, and the Netherlands in our study) is more conducive to decentralized decision‐making than the Napoleonic style (France, Spain, Italy, and Portugal in our study), which tends to be more centralized and top‐down (Painter and Peters 2010; Schoute and Budding 2017). This, in turn, may lead to more support for cost accounting in the Germanic tradition than in the Napoleonic one: in return for more detailed cost information, decision makers would be willing to delegate decision‐making powers.…”
Section: Theoretical Frameworkmentioning
confidence: 65%
“…While both the Germanic and Napoleonic traditions have been resistant to managerialist ideas, these have penetrated the former more extensively than the latter (Painter and Peters 2010; Peters 2008). Furthermore, the Germanic administrative tradition (Germany, Austria, and the Netherlands in our study) is more conducive to decentralized decision‐making than the Napoleonic style (France, Spain, Italy, and Portugal in our study), which tends to be more centralized and top‐down (Painter and Peters 2010; Schoute and Budding 2017). This, in turn, may lead to more support for cost accounting in the Germanic tradition than in the Napoleonic one: in return for more detailed cost information, decision makers would be willing to delegate decision‐making powers.…”
Section: Theoretical Frameworkmentioning
confidence: 65%
“…The findings of the current study imply that product diversity is an important factor for managers to use more cost pools and cost drivers. This finding can be justified as companies who have a mix of production lines would have different cost structures, operations, and prices, thus, it is recommended to have more wide range of cost drivers and rates to allocated manufacturing overhead costs accurately (Schoute & Budding, 2017). Therefore, it can be concluded that assigning overheads to activities is related to the level of diversity of products manufactured by the responding companies.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Com a finalidade de se ter um sistema eficiente, é necessário combinar os métodos de custeio com a teoria geral de finanças e avaliar corretamente a relação entre o custo e o benefício gerado (REMÍGIO, 2002). Salienta-se que são diversas características do sistema que definem seu nível de sofisticação, mas os três aspectos principais da 'sofisticação' do sistema são a sua complexidade, a sua inclusão (alocação) de custos indiretos e sua compreensibilidade pelos usuários não-financeiros (AL-OMIRI; DRURY, 2007;BRIERLEY, 2008;SCHOUTE;BUDDING, 2017). A complexidade, por sua vez, depende da quantidade de centros de custos, da quantidade e da natureza dos direcionadores de custos (BRIERLEY, 2008;TAYLES, 2005).…”
Section: De Acordo Com a International Federation Of Accountantsunclassified
“…A eficácia dele dependerá da intensidade do uso para diferentes propósitos e da satisfação dos usuários com o sistema (SCHOUTE;BUDDING, 2017). Quanto mais as entidades procuram atender às necessidades de informação dos usuários externos, mais complexo ele será (GEIGER;ITTNER, 1996;LAPSLEY;WRIGHT, 2004;SCHOUTE;BUDDING, 2017).…”
Section: De Acordo Com a International Federation Of Accountantsunclassified
See 1 more Smart Citation